Quantum target ranging for LiDAR - Giuseppe Ortolano; Ivano Ruo-Berchera (Physical Review Research)
We investigate Quantum Target Ranging in the context of multihypothesis testing and its applicability to real-world LiDAR systems. First, we demonstrate that ranging is generally an easier task compared to the well-studied problem of target detection. We then analyze the theoretical bounds and advantages of quantum ranging in the context of phase-insensitive measurements, which is the operational mode of most LiDAR systems. Additionally, we adopt a background noise model more suited to optical frequencies, as opposed to the typical single-mode thermal noise model used in quantum target detection theory. Our findings indicate that a significant exponential quantum advantage can be achieved using simple photon-counting receivers across a broad range of parameters, thereby validating the efficacy of the quantum approach for LiDAR implementations.